STEMR as an integrated Method in Learnings of Religion and Science at Pesantren-based Madrasa - Choeroni, Choeroni; Anwar, Khoirul; Sarjuni, Sarjuni; Nugroho, Bekti Taufiq Ari (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The emergence of the Revolutionary Era of Society 5.0 requires the mastery in science and technology. However, the development in science and technology has not been accompanied by the spiritual aspect as a balancing center. On the other hand, the institutions of religion education, have less participation in the world of education in madrasas and Islamic boarding schools. These institutions hold on to the very old traditions so that they are by far left behind from the touch of science and technology. Education in Islamic boarding schools (Madrasah) prioritizes learning in ulumus syar'i such as fiqh, fiqh proposals, interpretation, and memorizing the Qur'an. The development of science and technology has not been taken seriously by most of these institutions. This study is aimed to provide an overview of how the implementation of science learning uses the STEMR (Science, Technology, Engineering, Mathematics and Religion) method in learning natural science and mathematics in Pesantren-based Madrasa and how to integrate it in learning process. The method used in the study was field research with a qualitative descriptive analysis approach. The data were collected in three ways: observation, interview, and documentation. After conducting an in-depth study, it resulted that the implementation carried out was in the form of integrating Science, Technology, Engineering, Mathematics and Religion lessons by using information from Al-Qur'an verses to explaining scientific theory, both in class learning, practice and in composing scientific papers. After conducting an in-depth analysis, it shows that the STEMR method provides students with a great understanding in theory of sciences and the Qur'an. Yet, further research is needed to confirm the effects of scientific theory and the Qur'an.